The Anthropocene, War and the New Bestialization of the Human. A Popular Visual Media Perspective - Levente Palatinus, David (Itinerari, 2023)
Combining cultural theory- and screen research, this article examines the important but underexplored role ‘bestialization’ plays in the proliferation of contemporary films and television narratives about the relation between terrorism, war and the Anthropocene. I will argue that, on the one hand, film and television texts circulating cultural perceptions of conflicts in the Middle East mobilize conventional narratives of political justifications (or criticisms) of violence, but also subvert the conventions that function as vehicles of the cultural iconography of the war on terror. Similarly, these texts, as products of cultural symbolization, re-engage ethics and agency in the context of transgression, re-inscribing the logic of ‘us vs. them’ into processes of victimization, and to a sense of perpetual crisis in the Anthropocene epoch.